Technology and Pedagogic Trend of Education Process for Teachers in PGRI Organization - Muhammad Rusdil Fikri; Unifah Rosyidi; Siti Zulaikha (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to determine the pedagogic concepts related to technology to implement the teacher education process in the PGRI (Persatuan Guru Republik Indonesia) organization. Pedagogy in the global era requires a combination of technology for teaching and learning activities. The research method is qualitative through descriptive evaluative. Data collection techniques consist of interviews, observation, and documentation. Data analysis techniques include the reduction process data, data presentation, drawing conclusions and triangulation. The results showed that the PGRI organization had six programs to improve pedagogic competence, namely training, seminars, building partnerships, developing learning media, optimizing subject teacher group associations, and building social awareness. Various programs provide many activities related to pedagogy and technology.